2021
DOI: 10.3390/agronomy11081481
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Responses to Salinity of Soybean and Chenopodium album Grown in Single and Mixed-Species Hydroponic Systems

Abstract: Weeds account for losses in crop yields, and this event might be exacerbated by salinity. Therefore, we investigated the responses of Chenopodium album L. and soybean (Glycine max (L.) Merr.) to salt stress, as well as interferences between species. Ten-day old plants were grown for 1 week in a single- or mixed-species set-up, either with or without 100 mM of NaCl. C. album reduced the biomass of soybean similarly to salt stress, while its growth was unaffected under any condition. C. album decreased the crop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In general, salt stress can inhibit the growth performance of plants through water deficiency, ion ecotoxicity, and/or ion imbalance mediated by increased osmotic stress (Ghirardelli et al 2021, Huang et al 2021, Kumawat et al . 2022, Yu et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, salt stress can inhibit the growth performance of plants through water deficiency, ion ecotoxicity, and/or ion imbalance mediated by increased osmotic stress (Ghirardelli et al 2021, Huang et al 2021, Kumawat et al . 2022, Yu et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the allelopathic chemicals from the studied invasive species (especially S. canadensis ) may be more easily extracted and released from the leaves under salt stress-mediated osmotic stress, resulting in higher doses and subsequently more detrimental effects (Wang et al 2019a, Yu et al 2023). This phenomenon may also be attributed to the gradually increasing additional energy cost and the progressively decreasing nutrient uptake efficiency for the Seger-Segro of L. sativa under heavy salt stress compared to that under light salt stress (Ghirardelli et al 2021, Huang et al 2021, Kumawat et al 2022, Yu et al 2023). The consequences have confirmed the correctness of the Stress Hypothesis of Allelopathy (Reigosa et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The combined efforts from the public and private sectors have contributed to the ∼370% increase in soybean production from 1920 (740 kg ha −1 ) to the present day (3,470 kg ha −1 ), which resulted in total production of over 123 t in 2020 (Koester et al., 2014; Specht et al., 1999; Specht et al., 2014; USDA‐NASS, 2020; Vieira & Chen, 2021). However, biotic and abiotic stressors can cause significant reductions in yield in the United States (Allen et al., 2017; Bandara et al., 2020; Ghirardelli et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the southern United States, production losses of 12% have been estimated to be caused by SC in 2020 (Crop Protection Network, 2020). In addition, soil salinity is a major environmental stressor limiting plant growth and development, germination, seedling emergence, nodulation, and seed quality, resulting in significant yield reductions of up to 40% in soybeans (Do et al., 2019; Ghirardelli et al., 2021; Yang et al., 2017). Worldwide, salinity affects over 60 million ha (20%) of the irrigated land, of which ∼1.5 million ha of crop production are lost yearly due to extreme salinity conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to biotic stressors, soil salinity represents a major abiotic stressor that limits crop production by inducing ion toxicity and osmotic imbalance in soybean cultivars susceptible to salinity conditions, particularly in irrigated production systems (Bai et al., 2019; Chung et al., 2020). Studies have shown significant yield reductions of up to 40% in soybean due to the negative effect of salinity stress on seed germination, seedling emergence, root length, nodulation, plant height, and leaf size (Do et al., 2019; Ghirardelli et al., 2021; Yang et al., 2017). Because ∼5.2 million ha (23%) of the U.S. irrigated agricultural land is affected by salinity, deploying soybean cultivars with tolerance to salt represents one of the most effective strategies to minimize yield losses (Do et al., 2019).…”
Section: Introductionmentioning
confidence: 99%